2020
DOI: 10.3390/ma13235493
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Polyurethane Foams Reinforced with POSS-Impregnated Sugar Beet Pulp Filler

Abstract: Rigid polyurethane (PUR) foams were reinforced with sugar beet pulp (BP) impregnated with Aminopropylisobutyl-polyhedral oligomeric silsesquioxanes (APIB-POSS). BP filler was incorporated into PUR at different percentages—1, 2, and 5 wt.%. The impact of BP filler on morphology features, mechanical performances, and thermal stability of PUR was examined. The results revealed that the greatest improvement in physico-mechanical properties was observed at lower concentrations (1 and 2 wt.%) of BP filler. For examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 60 publications
4
23
1
Order By: Relevance
“…This, in turn, may be related to the fact that, on its surface, there are the most active cellulosic and lignin groups (e.g., hydroxyl groups), which, through interaction with polyester polyol, best disperse in polyol premixes. Similar results can also be found in earlier studies [ 21 , 22 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This, in turn, may be related to the fact that, on its surface, there are the most active cellulosic and lignin groups (e.g., hydroxyl groups), which, through interaction with polyester polyol, best disperse in polyol premixes. Similar results can also be found in earlier studies [ 21 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…Previous studies confirmed that the chemical treatments, especially alkalization, remove the waxy substances, which are responsible for the smooth surface of the filler. Due to this, the structure of the treated fillers becomes rough, which, in turn, may result in the better interlocking of the filler in the polymeric matrix [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the surface modification of the cellulosic filler seems to be necessary. Previous studies have reported different methods of filler modification, which include silane treatment [ 30 ], acetylation [ 31 ], or physical impregnation with selected flame-retardant compounds [ 32 ] or polysilsesquioxanes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%